PREDICTING THE BEHAVIOR OF IMPLANTS AND CROWNS USING THE FINITE ELEMENT METHOD IN VARIOUS OCCLUSION SCHEMES - Tashpulatova Kamilla Marat qizi (Western European Studies, 2025)
Implementation of functional occlusion management principles has important preventive significance in the manufacture of non-removable structures. Non-removable structures supported by implants play a special role, where an important condition is ensuring the maximum axial direction of chewing forces applied to the supporting elements [1, 2]. Occlusion, from the point of view of dentists, is of significant importance, especially in the restoration of defects in dental rows and changes in the position of teeth with a change in the angle of application of the load. In this case, it is important to understand how contact occurs in the frontal, sagittal planes during the parafunctional and functional activity of the chewing apparatus. In this regard, there are currently several main concepts of occlusion: the concept of group function on the laterotrucial side; the concept of balanced occlusion; the concept of the clitoral guide. The formation of functional occlusion during prosthetics with non-removable structures is the main task of optimal creation of the chewing surface of the replaced dental defect. Ensuring the safe use of orthopedic structures is necessary to protect the supporting elements from excessive loads, as well as to minimize their movement during the adaptation process [3, 4]. Digital methods for manufacturing non-removable structures also allow for recording the volume of movement of support elements and structures. This will allow for the creation of software for predicting the displacement of support teeth and taking into account the obtained results when modeling non-removable structures. An important aspect requiring special attention is both the location of the supporting element and the nature of the support, i.e., the implant or natural tooth. Since the degree of mobility of these elements is different, the reaction to overload is also different [5, 6]. The chewing system adapts relatively easily to changes in occlusal relationships during short periods of no-load. When dynamic equilibrium is disrupted (tooth preparation), the vertical displacement is 40 μm per day, while the horizontal displacement is 30 μm per day. This process is reversible when manufacturing an orthopedic structure in the shortest possible time or when using temporary crowns. At the same time, the formation of a secure occlusion occurs functionally.
Keywords: functional occlusion; dynamic equilibrium; horizontal displacement